Profesionalisme Keinsinyuran - Jeffry Yuliyanto Waisapi (Formosa Journal of Social Sciences (FJSS), 2022)
The profession of a civil engineer or civil engineer in a project has a very broad impact on people's lives. A civil engineering graduate is required to have professional expertise and high dedication in carrying out his work so that he can produce quality products and serve the needs of the community, especially in the infrastructure sector. Written and Professional Engineering Ethics Based on the formulation of the problem, it is hoped that the following objectives can be achieved: Understanding what a profession is and what its characteristics are, knowing the code of ethics of the engineering profession in realizing the needs of society. Objectives Introduction and understanding of the ethics of the engineering profession needs to be done as early as possible, even some technical colleges have included it in the curriculum and special courses. The Accreditation Board for Engineering and Technology (ABET) itself specifically provides accreditation requirements which state that every engineering student must fully understand the ethical characteristics of the engineering profession and its application. in their field and must always think positively by upholding professional ethics and integrity. The civil engineering profession is a civil engineering job which in its implementation requires expertise to serve the needs of the community in the infrastructure sector. A profession usually has a professional association, a code of ethics, and a certification and licensing process that is specific to that profession. In the work of an engineering graduate (engineer) on a project, he must have the requirements as a competent and academically accountable professional in order to produce quality products, especially in the infrastructure sector so that it is expected to serve the needs of the community as well as possible. The existence of a code of ethics that regulates the actions of a civil engineer or engineering graduate to avoid all forms of action that will harm himself, society and the environment